The impact of social and contractual enforcement on reseller performance: the mediating role of coordination and inequity during adoption of a new technology. Issue 6 (4th July 2016) - Osmonbekov, Talai; Gregory, Brian; Chelariu, Christian; Johnston, Wesley J.
Abstract : Purpose: The purpose of this research is to examine the impact of social and contractual enforcement on the performance of the B2B relationship. The research also tests the mediating role of perceived inequity and coordination. Design/methodology/approach: A survey methodology was used to obtain responses from 224 decision makers at reseller organizations. The data was analyzed using structural equation modeling. Findings: It was found that both social and contractual enforcement impact relationship performance. Perceived inequity and coordination are important moderators of those relationships, as social enforcement increases coordination and reduces perceived inequity while contractual enforcement increases perceived inequity. Originality/value: While previous studies examined enforcement impact on coordination and conflict, this study links it to relationship performance. Importantly, enforcement's relationship with perceived inequity is also examined in the context of business-to-business relationship.